A quest for indigenous truffle helper prokaryotes - Gryndler, Milan; Soukupová, Lucie; Hršelová, Hana; Gryndlerová, Hana; Borovička, Jan; Streiblová, Eva; Jansa, Jan (Environmental microbiology reports, 2013)
Tuber aestivum is the most common European truffle with significant commercial exploitation. Its production originates from natural habitats and from artificially inoculated host tree plantations. Formation of Tuber ectomycorrhizae in host seedling roots is often inefficient. One possible reason is the lack of indigenous associative microbes. Here we aimed at metagenetic characterization and cultivation of indigenous prokaryotes associated with T. aestivum in a field transect cutting through the fungus colony margin. Several operational taxonomic units (OTUs) showed close association with the T. aestivum in the ectomycorrhizae and in the soil, but there was no overlap between the associative prokaryotes in the two different habitats. Among those positively associated with the ectomycorrhizae, we identified several bacterial genera belonging to Pseudonocardineae. Extensive isolation efforts yielded many cultures of ectomycorrhizae-associative bacteria belonging to Rhizobiales and Streptomycineae, but none belonging to the Pseudonocardineae. The specific unculturable Tuber-associated prokaryotes are likely to play important roles in the biology of these ectomycorrhizal fungi, including modulation of competition with other symbiotic and saprotrophic microbes, facilitation of root penetration and/or accessing mineral nutrients in the soil. However, the ultimate proof of this hypothesis will require isolation of the microbes for metabolic studies, using novel cultivation approaches.
Keywords: kořeny rostlin; Symbiosis; Ascomycota; Soil Microbiology; stanovení celkové genové exprese; Mycorrhizae; Gene Expression Profiling; mykorhiza; Plant Roots; půdní mikrobiologie; Metagenome; symbióza; metagenom; Actinomycetales